Optimizing Drawing Ability Through Working Memory Effects: Methods for Novice and Expert Learners - Agussalim Djirong; Faizal Erlangga Makawi (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This research aims to develop two model-drawing methods based on students’ levels of competency, guided by a psychological approach to working memory. The study adopts a qualitative method with a case study design. Observations were carried out by analyzing six samples of model drawings produced by students in the Visual Arts Education program, Faculty of Art and Design. The drawings were categorized into two levels, expert and novice, based on students’ performance in proportion, coloring, and detail. The findings show that (1) three students belong to the expert level, producing highly impressive model drawings whose proportions, coloring, and details are close to perfection; (2) three students fall into the novice level, with their proportions, coloring, and object forms still at a minimal or below-standard quality; and (3) one commonly used method is found to be unsuitable for all learners. Therefore, this research proposes two model-drawing methods according to students’ competency levels: the Golden Ratio technique for expert-level students and a proportion-and-shape-based technique for novice learners.